2008
DOI: 10.1111/j.1537-2995.2008.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on the feasibility of autologous cord blood transfusion for anemia of prematurity

Abstract: Autologous RBCs derived from UCB could not replace 50 percent of allogeneic transfusions due to the low UCB volumes collected and subsequent low product availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 35 publications
1
57
2
Order By: Relevance
“…A few reports have used a modification of this practice for acute administration after birth, aimed at immediate volume expansion of ill and small neonates 82 94100. Most of these reports describe processing and storing the fetal blood banking, in case a transfusion is needed in the subsequent days or weeks 82 9699. Reports from Japan101 and Germany102 describe successful cord/placental blood transfusion for neonates with surgical problems.…”
Section: New Methods Aimed At Reducing the Need For Transfusionmentioning
confidence: 99%
“…A few reports have used a modification of this practice for acute administration after birth, aimed at immediate volume expansion of ill and small neonates 82 94100. Most of these reports describe processing and storing the fetal blood banking, in case a transfusion is needed in the subsequent days or weeks 82 9699. Reports from Japan101 and Germany102 describe successful cord/placental blood transfusion for neonates with surgical problems.…”
Section: New Methods Aimed At Reducing the Need For Transfusionmentioning
confidence: 99%
“…In fact, in the past, other authors have described the clinical feasibility of cord blood for the therapy of anemic neonates, but only for autologous use [7,8,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been explored to prevent or even to reduce the threshold and the frequency of RBC transfusions. Among these, umbilical cord blood (UCB) collection and processing to obtain RBC products for autologous transfusion have been extensively investigated [7,8,9,10,11,12]. The refinement of techniques of collection, processing and storage of UCB allowed the production of UCB-RBC units suitable for clinical use [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The practice of transfusions of RBCs derived from umbilical cord blood to treat neonatal anemia has recently gained a lot of interest [2635]. A number of studies have demonstrated that transfusions of autologous cord RBCs are both safe and effective in the treatment of anemic neonates [26–32].…”
Section: Introductionmentioning
confidence: 99%